2021
DOI: 10.1044/2021_jslhr-20-00462
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Validation and Normative Values for the German Vocal Tract Discomfort Scale

Abstract: Purpose The Vocal Tract Discomfort Scale (VTD Scale) is a self-rating questionnaire investigating physical symptoms in the larynx associated with vocal pathology. The aim of this work was to investigate the reliability, validity, sensitivity, and specificity of the first German version and to provide normative data with thresholds for pathology and a scaling scheme. Study Design A retrospective multicenter study was performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
3
0
2
Order By: Relevance
“…For the self-assessment of the speaking voice, we used the Polish version of the Vocal Tract Discomfort scale. Given the absence of universally agreed-upon normative values for the VTD scale, our investigation drew comparisons between the outcomes we obtained and those reported in prior studies available in the literature (66)(67)(68). In a study conducted on a general population, Robotti et al (66) reported mean VTDS scores of 15.3 ± 8.7 for the Frequency subscale and 15.5 for the Severity subscale in a group of dysphonic individuals.…”
Section: Self-assessment Of Voicementioning
confidence: 86%
See 1 more Smart Citation
“…For the self-assessment of the speaking voice, we used the Polish version of the Vocal Tract Discomfort scale. Given the absence of universally agreed-upon normative values for the VTD scale, our investigation drew comparisons between the outcomes we obtained and those reported in prior studies available in the literature (66)(67)(68). In a study conducted on a general population, Robotti et al (66) reported mean VTDS scores of 15.3 ± 8.7 for the Frequency subscale and 15.5 for the Severity subscale in a group of dysphonic individuals.…”
Section: Self-assessment Of Voicementioning
confidence: 86%
“…Additionally, we related the total VTDS scores reported by CCM singers in our study to the results presented by Lukaschyk et al who set normative values for the German VTDS. They proposed VTDS ranges as follows: no (score: 0–13), mild (score: 14–26), moderate (score: 27–40), and severe (score: 41–96) disorder ( 68 ). In light of these data, the CCM singers with the VTD mean total score of 26.66 ± 17.60 fall into the mild/moderate voice disorder category.…”
Section: Discussionmentioning
confidence: 99%
“…Die deutsche Übersetzung der Vocal Tract Discomfort Scale (VTD) 15 dient der Selbsteinschätzung und Bewertung von acht Symptomen hinsichtlich Häufigkeit und Schweregrad auf einer Skala von 0 (nie) bis 6 (immer/extrem). Sie weist eine ausgezeichnete Reliabilität und Validität auf und wurde an 571 Personen normiert.…”
Section: Materials Und Methodenunclassified
“…The items included in the EASE-3 have clear connections with known symptoms of vocal fatigue and functional disorder such as huskiness, dryness, scratchiness, and strain [98], some of which have also been included in the widely used Vocal Tract Discomfort Scale [12,[99][100][101]. In the EASE-3 these sensations are reported in Q1 (My voice is husky) and Q2 (My voice is dry/scratchy).…”
Section: Symptoms Of Vocal Fatigue and The Ease-3mentioning
confidence: 99%